Transcriptome analysis of Thevetia peruviana cell suspensions treated with methyl jasmonate reveals genes involved in phenolics, flavonoids and cardiac glycosides biosynthesis - Cuaspud, Olmedo; Mendoza, Dary; Navarro, Gigliola; Arias, Juan; Calle, Isabel; Arcila-Galvis, Juliana; Arango Isaza, Rafael Eduardo (Frontiers in Plant Science, 2025)
Thevetia peruviana (Pers.) K. Schum is a tropical shrub with recognized ethnomedicinal applications associated with the presence of secondary metabolites (SMs), which exhibit cardiotonic, antioxidant, antimicrobial and anticancer activities. Previous studies have shown that methyl jasmonate (MeJA), when exogenously applied to T. peruviana cell cultures, activates the production of phenolic compounds (PCs), flavonoids (Fvs) and cardiac glycosides (CGs); however, the biochemical mechanisms involved in the MeJA-regulated biosynthetic pathways remain unknown. To deepen our understanding of the effect of MeJA on the secondary metabolism of T. peruviana, transcriptome sequencing was performed on suspension cell culture. A first draft transcriptome of T. peruviana was obtained, with an average N50 length of 3570 bp, comprising a total of 83126 unigenes. Differential gene expression analysis was conducted to evaluate the effects of treatment with 3 µM MeJA. In MeJA-treated cells, genes involved in the glycolytic pathway were upregulated, providing the necessary energy and metabolic precursors for SMs biosynthesis. Additionally, key genes in the biosynthesis of PCs (HST, ALDH2C4), Fvs (SHT, FLS/F3H, FaGT6) and CGs (ISPF, TPS, SQS1, IPP2, CYP710A3, SCL14, DWF1) were significantly upregulated in response to MeJA. Other notable effects of MeJA included the regulation of transcription factors (bHLH, MYB, bZIP, WRKY and ERF), which are involved in the biosynthesis of target metabolites. This de novo assembly of T. peruviana transcriptome provides a valuable resource for future research in functional genomics and metabolic engineering of bioactive SMs. Additionally, it offers new insights into the molecular mechanisms underlying the plant’s response to MeJA, paving the way for targeted strategies to enhance the production of pharmacologically relevant compounds.